ผลของตัวเร่งปฏิกิริยาและตัวทำละลายต่อการแปรรูปถ่านหินเป็นของเหลว - ศิริน เมธาคุปต์ (จุฬาลงกรณ์มหาวิทยาลัย, 2004)
Liquefaction of Mae Moh Lignite was performed in a batch reactor apparatus using a mixture of toluene and tetralin as solvent. The experiments were carried out to investigate the effects of temperature, initial hydrogen pressure and solvent/coal ratio on coal conversion, liquid yield and liquid composition. The effect of catalysts ion sulfur, ion nickel and NiMo was also studied. In the absence of catalyst, the yield of coal liquid at temperature of 410 ํC, initial hydrogen pressure of 12 MPa and solvent/coal ratio of 1, reached a maximum 53.8% (daf) which included naphtha 3.5%, kerosene 61.3%, light gas oil 12.6%, gas oil 3.2% and long residue 19.4%. At the same condition and with the presence of NiMo catalyst, the liquid yield reached 60.7 wt% (daf) which included naphtha 2%, kerosene 72.8%, light gas oil 14.9%, gas oil 2.4% and long residue 7.9%. For GC/MS analysis, the fraction of kerosene composed of Tetralin, Naphthalene, Cycloheptasiloxane dodecamethyl-, Dodecanoic acid methyl ester, Cycloheptasiloxane tetradecamethyl-, Dodecanoic acid ethyl ester, Methyl tetradecanoate and Dibutyl phthalate